2013
DOI: 10.1021/om4002796
|View full text |Cite
|
Sign up to set email alerts
|

Silylium Ion Promoted Reduction of Imines with Hydrosilanes

Abstract: The silylium ion promoted reduction of imines yielding the corresponding amines is reported. Both tert-butylferrocenylmethylsilane and triethylsilane are efficient hydride donors for the reduction of intermediate silyliminium ions, thereby regenerating the catalytically active silylium ion and closing the catalytic cycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 38 publications
1
27
0
1
Order By: Relevance
“…[44] Oestreich has recently proposed that backside attack of a [R3Si-H-SiR3] + species by an imine could be a viable pathway for silylium-catalyzed imine hydrosilation, provided that the silicon substrate is not sterically hindered. [45] Thorough mechanistic studies are needed to assess whether Si-H-Si species are viable intermediates during catalysis.…”
Section: Silicon Catalystsmentioning
confidence: 99%
“…[44] Oestreich has recently proposed that backside attack of a [R3Si-H-SiR3] + species by an imine could be a viable pathway for silylium-catalyzed imine hydrosilation, provided that the silicon substrate is not sterically hindered. [45] Thorough mechanistic studies are needed to assess whether Si-H-Si species are viable intermediates during catalysis.…”
Section: Silicon Catalystsmentioning
confidence: 99%
“…Most commonly used and well-studied photo-initiatable catalysts are platinum-based ones such as a A novel method for obtaining α-silyl carbonyl products using B(C 6 F 5 ) 3 as catalyst was reported by Kim and Chang [69]. Unlike previously reported hydrosilylations of unsaturated polar bonds (such as carbonyls, imines, and nitriles [70][71][72]), the authors demonstrated the feasibility of the chemoselective α-silylation of conjugated esters and amides, in which the carbonyl group was left intact (Figure 29). According to preliminary mechanistic studies, the reaction proceeds in two steps, namely rapid 1,4-hydrosilylation of conjugated carbonyls and slow silyl group migration of a silyl ether intermediate.…”
Section: Light-initiated Hydrosilylation Reactionsmentioning
confidence: 99%
“…Next, the intramolecular electrophilic addition of the silyl cation moiety of A to the C-C triple bond produces ethenyl carbocation B, which is stabilized by the β-silyl effect of the trimethylsilyl group. Finally, the hydride abstraction of B from another 1 affords benzosilole 2 and regenerates intermediate A [27][28][29], which acts as a chain carrier. from 1f being less stable than those derived from 1a-e, which are stabilized by double β-silyl effects.…”
Section: Methodsmentioning
confidence: 99%